Endogenous Growth Theory: The Influence of Health Budget Allocation and Financial Sector Growth on the Indonesian Economy - Wardhani, Dyah Ciptaning Lokiteswara Setya (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study delves into the application of Endogenous Growth Theory to the Indonesian context, focusing on the interplay between health budget allocation and the growth of the financial sector in shaping the country's economy. Endogenous Growth Theory posits that economic growth can be internally driven by factors such as human capital accumulation, technological progress, and institutional development. Through empirical analysis, this research examines how the allocation of resources to the health sector and the expansion of the financial industry impact Indonesia's economic performance. By employing quantitative methods and econometric models, the study elucidates the extent to which these factors contribute to economic growth and development. The findings shed light on the importance of targeted budgetary allocations and financial sector policies in fostering sustained and inclusive economic progress in Indonesia